The Impact of Climate Change on Bivalve Farming: Combined Effect of Temperature and Salinity on Survival and Feeding Behavior of Clams Ruditapes decussatus - Rato, Ana; Joaquim, Sandra; Matias, Ana Margarete; Roque, Cláudia; Marques, António; Matias, Domitília (Frontiers in Marine Science, 2022)
European clam (Ruditapes decussatus) is one of the most relevant emergent bivalve species from the aquaculture sector in Europe with high economic value. Climate changes represent a potential limiting factor to this activity, directly interfering with the survival and behavior of bivalves. Severe fluctuations in temperature along with periods of heavy rainfall or periods of drought that significantly change the salinity can promote physiological stress in bivalves, resulting in changes in physiological and behavioral responses and, in extreme cases, leading to high mortalities. This study aimed to evaluate the combined effect of temperature and salinity on mortality and feeding behavior of R. decussatus. Juveniles and adults were exposed to combined ranges of temperature (5°C–35°C) and salinity (0–40). Mortality and feeding behavior were registered every 24 h of each 120-h trial. A control temperature range was set between 15°C and 23°C, where mortality and feeding behavior were considered as the normal scenario. Our data suggested salinity 15 as a “turning point,” a point from which occurred distinct patterns in mortality and feeding behavior. The results evidently indicate that abrupt reductions in salinity and sharp increases in temperature will lead to high mortality of R. decussatus. Juveniles were revealed to be more sensitive to the increase of temperature in a less saline environment, to suffer greater and faster mortalities, and to be more resistant to extremely high temperatures under more saline conditions. The high temperatures and sporadic heavy rainfall that are predicted to occur in the south of Europe due to climate changes will contribute to compromise the recruitment of European clam, thus threatening the production of this species and consequently impacting the economic sector.